Structure Design and Finite Element Analysis of a Rope Traction Upper Limb Rehabilitation Robot - Yu Junwei; Xu Hongbin; Xu Taojin; Zheng Chengjie; Lu Shiqing (Jixie chuandong)
Aiming at the problem that the upper limb rehabilitation robot has secondary damage caused by inertial impact,a new mechanism of a rope traction upper limb rehabilitation robot is designed by using the hybrid mechanism. To ensure the safety and stability of the rehabilitation robot,the static strength analysis and modal analysis of the structure of the upper limb rehabilitative robot is carried out by using ANSYS Workbench.Moreover,the multi-objective genetic algorithm is applied to the lightweight optimization design of the support frame. The result shows that the total mass of support frame after optimization is comparatively 48% less than before. At the same time,the inherent characteristic of the whole frame is obtained,which is prepared for the later control strategy.